Why are our trees sick? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Sister Hilary Glaffey (PO Box 824, Makurdi, Benue State, Nigeria) asks if any readers 'have noticed a disease affecting the Parkia clappertonia and Prosopis africana trees in West Africa? These trees are economically and nutritionally very...